Refusing Medication Therapy in Involuntary Inpatient Treatment—A Multiperspective Qualitative Study - Jaeger, Susanne; Hüther, Franziska; Steinert, Tilman (Frontiers in Psychiatry, 2019)
Objective: Between June 2012 and February 2013, two decisions by the German Federal Constitutional Court restricted the so-far common practice to use involuntary medication in inpatients who were involuntarily hospitalized. Up to then, involuntary medication was justified by a judge’s decision on involuntary hospitalization. It could be applied according to clinical judgment even against the declared will of a patient. Since then, all domestic laws related to involuntary treatment had to be revised. For several months, involuntary medication was allowed only in an emergency. We were interested in the impact of the changed legal framework on the experiences of inpatients, their relatives, and clinical professionals during that time. Methods: Thirty-two interviews were analyzed qualitatively using a grounded theory methodology framework. Results: As a consequence of the restrictions to involuntary medication, special efforts by nursing and medical staff were required concerning de-escalation, ward management, and the promotion of treatment commitment in inpatients who refused medication. Family caregivers were also under strong pressure. They wanted to help and to protect their relatives, but some also welcomed the use of coercion if the patient refused treatment. Most of the interviewed patients had not even noticed that their rights to refuse medication had been strengthened. They complained primarily about the involuntary hospital stay and the associated limitations of their everyday lives. While patients and family members evaluated the refusal of medication from a biographical perspective, the mental health care professionals’ focus was on the patients’ symptoms, and they understood the situation from a professional perspective. It was obvious that, in any of the four perspectives, the problem of feeling restricted was crucial and that all groups strived to gain back their scope of action. Conclusion: The temporary ban on involuntary medication questioned the hitherto common routines in inpatient treatment, in particular when patients refused to take medication. Each of the different groups did not feel good about the situation, for different reasons, however. As a consequence, it might be indispensable to increase awareness of the different perspectives and to focus the efforts on the establishment of nonviolent treatment structures and practices.